Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review. Issue 8 (23rd March 2023) - Ravindran, Nevetha; Kumar, Sandhya; M, Yashini; S, Rajeshwari; C A, Mamathi; Thirunavookarasu S, Nirmal; C K, Sunil
Abstract: Food safety is the prime area of concern that builds trust. With the prevailing advancements, it has become facile to ensure safety in almost all aspects. Technology has grown from tedious lab techniques to modern chromatographic techniques and immunoassays, progressed with more precise and rapid sensing through the advent of Biosensors. Biosensors provide an automated technology by presenting superfast, nondestructive and cost-effective detection in food analysis. SPR biosensor is an optical biosensor known for its versatility and has wider applications in food testing and analysis. It has an optical system for excitation and interrogation of surface plasmons, and a biomolecular recognition element to detect and seize the target analyte present in a sample. The optical signal detects the binding analyte, on the recognition element, which results in a change in refractive index at the surface and modifies the surface plasmons' propagation constant. SPR aids in label-free detection of various components such as adulterants, antibiotics, biomolecules, genetically modified foods, pesticides, insecticides, herbicides, microorganisms and microbial toxins in food and assures safety. The distinct advancements of SPR in food analysis have been found and discussed. The review also provides knowledge on the advantages and the key challenges encountered by SPR. Graphical Abstract: UF0001